Comparison selection: An approach to the study of consumer judgment and choice. Issue 1 (12th October 2012) - Simonson, Itamar; Bettman, James R.; Kramer, Thomas; Payne, John W.
Abstract: We introduce an alternative perspective on the study of consumer judgment and decision making, which is based on the notion that judgment and choice problems consist of comparisons that decision makers might select. Our new perspective proposes that if we can predict the likelihood that particular comparisons will become focal in a judgment or choice task, we will be able to gain a better understanding of and anticipate the resulting effect. Building on related literatures, we propose that comparison selection is driven by the task's latitude of acceptance (LOA) and comparison fluency (i.e., the overall ease of making that comparison). The task's LOA curve represents the range and concentration of potentially acceptable comparisons, whereas comparison fluency refers to the salience and ease of making the comparison. We illustrate our approach using previously studied problems (e.g., choice, variety seeking, the "jacket and calculator" problem, and contingent valuation) as well as new empirical tests.